Fragmented QRS formation may be associated with increased carotid intima-media thickness in patients with end-stage renal disease - Doğan, Tolga; Yetim, Mucahit; Doğan, İbrahim and Kalçık, Macit and Bekar, Lütfü and Celık, Oguzhan and Karavelioğlu, Yusuf (The European Research Journal, 2021)
Objectives: The aim of this study was to evaluate the relationship between carotid intima-media thickness and the presence of fragmented QRS in end-stage renal disease patients. Methods: The study included 100 end-stage renal disease patients who received hemodialysis treatment. Two groups were formed according to the presence of electrocardiography and fragmented QRS: the fragmented QRS (+) (Group I) and the fragmented QRS (-) (Group II). Echocardiographic measurements of the cardiac dimensions and carotid intima-media thickness were examined. Results: The study population included 41 end-stage renal disease patients with fragmented QRS (48.8% male) and a control group of 59 end-stage renal disease patients without fragmented QRS (35.6% male) on electrocardiography. Left ventricular end systolic diameters (p = 0.012),left ventricular end diastolic diameters (p < 0.001), left atrial diameter (p = 0.001), interventricular septal thickness (p < 0.001), posterior wall thickness (p < 0.001) and left ventricular hypertrophy (p < 0.001), blood urea nitrogen (p = 0.011), creatinine (p = 0.014), uric acid (p < 0.05) and parathyroid hormone (p < 0.05) values were found to be significantly increased in the fragmented QRS (+) group. The right and left carotid intima-media thickness values were significantly higher in fragmented QRS (+) patients than fragmented QRS (-) patients (right:[0.81 ± 0.19] vs [0.62 ± 0.14] mm, p < 0.001) and left: [0.83 ± 0.19 vs 64 ± 0.14], p < 0.001; respectively). Conclusions: In end-stage renal disease patients, the presence of fragmented QRS, left ventricular hypertrophy and increased carotid intima-media thickness are important markers in the evaluation of the inflammatory process of atherosclerosis.